Pengembangan E-LKPD berbasis model discovery learning pada materi termokimia untuk mengukur keterampilan sains siswa - Vadilla, Nur (ARKA INSTITUTE, 2022)
This research aims to develop a Discovery Learning-based E-Learners' Worksheet (E-LKPD) for thermochemistry material as an assessment of students' science skills at the high school level. With the Research and Development (R & D) approach of the 4-D model, the research involves the Defining, Designing, Developing, and Deploying stages, and uses the liveworksheet application. Validation was conducted by four validators, two for material and two for media, with average validity results of 89.5% and 81% respectively, categorized as very valid. The trial was conducted with 34 students, accompanied by a response questionnaire from two teachers and students. Teacher responses reached 94%, indicating a high level of feasibility and practicality. Learners' response reached 94.9%, indicating significant attractiveness. Measurement of students' science skills, through questions in the E-LKPD, showed an average value above the Minimum Completion Criteria (KKM) (>75). Overall, this Discovery Learning E-LKPD for thermochemistry is considered valid and effective to be used in learning chemistry at the high school level.